The Influence of Online Service Quality, Online Trust, and Electronic Word of Mouth on Online Hotel Reservation Decisions in Tiket.Com in DKI Jakarta - Siti Mariah Ulfah; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of Online Service Quality, Online Trust, Electronic Word Of Mouth on online hotel reservation decisions at tiket.com in DKI Jakarta. The sample in this study were 100 respondents who had made online hotel reservation transactions at least 2 times using tiket.com. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 25.0 program. From the results of multiple linear regression analysis, using the t test where online service quality (X1) has a positive and significant effect on reservation decisions with a score of 3.082 > 1.984. Online Trust (X2) has a positive and significant effect on Behavioral Intention with a score of 3.155 > 1.984 and E-Wom (X3) has a positive and significant effect on Behavioral Intention with a score of 2.057 > 1.984. So it can be concluded that online service quality, online trust, and electronic word of mouth have a positive effect on reservation decisions.